The practicalities of police research - Martin, Denise (Introduction to policing research, 2024)
This chapter considers the practical dilemmas and challenges of engaging in police research. The types and volume of police-related research have grown considerably in recent years but as well as understanding methodological choices and questions, there are other decisions, and dilemmas that researchers face. This can be dependent on the purpose of that research and the position of the researcher, and the goals of that research. While this chapter aims to address more of the technical issues, it also reflects on the different paths and challenges that researchers might face and must consider in their attempts to engage with police-related research. This chapter approaches this from a position of experience of being involved in police research and discusses some of the critical issues that researchers may encounter when considering how to approach and undertake research into, on and with police organisations.